2007
DOI: 10.1038/nmat1963
|View full text |Cite
|
Sign up to set email alerts
|

Electronic control of Ca2+ signalling in neuronal cells using an organic electronic ion pump

Abstract: Cells and tissues use finely regulated ion fluxes for their intra- and intercellular communication. Technologies providing spatial and temporal control for studies of such fluxes are however, limited. We have developed an electrophoretic ion pump made of poly(3,4-ethylenedioxythiophene) doped with poly(styrene sulphonate) (PEDOT:PSS) to mediate electronic control of the ion homeostasis in neurons. Ion delivery from a source reservoir to a receiving electrolyte via a PEDOT:PSS thin-film channel was achieved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
395
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 371 publications
(410 citation statements)
references
References 42 publications
3
395
1
1
Order By: Relevance
“…Electrophoretic delivery of ions and charged biomolecules is attractive since it induces little convection, does not rely on moving mechanical parts and the delivered amount of substance can be correlated to the electric current [1][2] . Delivery rate and temporal control can be mediated through the applied voltage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophoretic delivery of ions and charged biomolecules is attractive since it induces little convection, does not rely on moving mechanical parts and the delivered amount of substance can be correlated to the electric current [1][2] . Delivery rate and temporal control can be mediated through the applied voltage.…”
mentioning
confidence: 99%
“…When hydroxide ions are transported from the emitter into the junction the proton concentration decreases together with IC. We have recently shown that organic conducting materials can be used in vitro and in vivo to translate electric signals into precise delivery of positively charged chemical messengers 2,[23][24] . To evaluate if the present npn-IBJT can be used in a corresponding manner, i.e.…”
mentioning
confidence: 99%
“…[1][2] One example is organic electronic ion pumps, 15 which are able to precisely control the flow of ions between two reservoirs, and have been used to pump neurotransmitters and stimulate cochlear cells in the inner ear of a guinea pig. [3][4][5] Another example is organic electrochemical transistors (OECTs) that are being developed for a variety of biosensing 20 applications, including the detection of ions, [6][7][8] metabolites (such as glucose 9 and lactate 10 ) and antibodies. 11 Originally developed by Wrighton in the 80's, 12 OECTs consist of a conducting polymer film (channel of the transistor) in contact with an electrolyte.…”
mentioning
confidence: 99%
“…Silicon nanowire and carbon nanotube transistors integrated with enzymes, antibodies, and lipid bilayers use ions to gate electronic currents and record biological reactions in the intracellular and extracellular space 2, 3, 9, 10, 11, 12, 13, 14, 15, 16. Organic polymers with mixed electronic and ionic conductivity integrated in electrodes and electrochemical transistors transduce ionic to electronic currents and amplify small biological signals3, 17, 18, 19, 20, 21, 22 In addition, organic iontronics locally deliver ions and neurotransmitters in the extracellular space to affect cell and tissue function 23, 24, 25, 26. Batteries with biocompatible materials are used for giving energy to these systems 27.…”
Section: Introductionmentioning
confidence: 99%